PERGESERAN TRADISI PEMBUATAN JALUR PADA MASYARAKAT KABUPATEN KUANTAN SINGINGI - Rapni Yelti; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: In making the pathway, it turns out that there are also elements of Malay culture, namely pantun. Pantun is not only used in a variety of social activities, but also in the pathway culture. The Pantun is the most widely known form of Malay literature. In the past pantun was used to complete daily conversation. Even now most Malay people in the countryside still use it. Starting from the background of the problem, the writer can formulate the problem, namely